2017
DOI: 10.14198/jhse.2017.123.02
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between action inhibition and athletic performance in elite badminton players and non-athletes

Abstract: Racket sports are among the most popular sports in the world. They require higher-order cognitive processes to execute complex actions to achieve successful performance on the court. Action inhibition is the ability to suppress ongoing actions; it is crucial to achieving higher levels of sports performance. The aim of the present study was to investigate the effect of expertise on action inhibition in badminton players and non-athletes. Current study recruited forty-two professional badminton players and match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Our results adds to previous studies pointing towards that ball sports played at higher level 15,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] , including elite soccer 15,16,[25][26][27][28] , are associated with better EF than when played at lower level. Also, the results are in Figure 3.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results adds to previous studies pointing towards that ball sports played at higher level 15,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] , including elite soccer 15,16,[25][26][27][28] , are associated with better EF than when played at lower level. Also, the results are in Figure 3.…”
Section: Discussionsupporting
confidence: 81%
“…In line with this hypothesis, we have previously shown that adult elite soccer players have significantly better EF compared to sub-elite players 15 . Following this study, a similar link between EF and level of play has been suggested in several soccer studies 16,[24][25][26][27][28] as well as in studies of other ball sports 24,[29][30][31][32][33][34][35][36][37][38] . As some studies have not identified a difference in EF between elite and semi-elite players in ball sports 39,40 this question is still under debate.…”
supporting
confidence: 77%
“…We have, for example, previously postulated that well-developed EF are important in elite team ball-sports since a large amount of information must quickly be processed in a constantly changing environment (Vestberg et al, 2012(Vestberg et al, , 2017(Vestberg et al, , 2020. In line with those ideas, it has been suggested that measures of EF, and especially HEF, have an important role in soccer (Verburgh et al, 2014(Verburgh et al, , 2016Huijgen et al, 2015;Vestberg et al, 2017Vestberg et al, , 2020Krenn et al, 2018;Sakamoto et al, 2018;Schumacher et al, 2018;Scharfen and Memmert, 2019) and other ball sports (Alves et al, 2013;Faubert, 2013;Wang et al, 2013Wang et al, , 2016Lundgren et al, 2016;Alarcón et al, 2017;Liao et al, 2017;Ishihara et al, 2018;Wylie et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Inhibitory control, which encompasses both response inhibition and response re-engagement, plays an essential role in goal-directed behavior in daily life 1 as well as in sports. Previous studies have described a positive relationship between sport performance and inhibitory control 2, 3, 4, 5, 6. However, most of these studies focused on response inhibition, which refers to the ability to stop an ongoing or planned action that is no longer appropriate,7, 8, 9 rather than re-engagement to an alternate response.…”
Section: Introductionmentioning
confidence: 99%